The coming-out process of gay adolescents in the University of the Philippines, Miag-ao, Iloilo - Deysolong, Recalynn M.
This study aims to know the coming-out process of gay adolescents in the University of the Philippines, Miag-ao. It has the following specific obejctives: first, to describe the stages of the coming-out process or disclosure of one's identity of gay adolescents. Second, to idetify the major influences that trigger gay adolescents to come out. Third, to know in what stage of the coming-out process these gay adolescents are in now. Fourth is to find out what happened to the gay adolescents after they come-out. The respondents of this study consisted of fifteen (15) gay adolescents. They were all bonafide students of the University of the Philippines, Miagao and were selected based on the following criteria: he considers himself gay and he has come-out or disclosed his sexuality publicly during his adolescent age. A snowball sampling method or chain referral was used in the process of acquiring the needed respondents. The researchers conducted the in dept interviews using an interview schedule as a guide. Findings showed that most of the respondents are still in the third stage, which is disclosure to others, and some are already in the fourth stage, that is coming-out of the closet. Most of them were not yet able to disclose their sexual orientation to their families. Thus, they were not yet able to disclose their sexual orientation to their families. Thus, they were referred to as "half-out" wherein they disclosed their sexual orientation only to close friends but act straight in the company of family and strangers.